Phenotypic detection of Metallo- and AmpC β-lactamases producing strains of P. aeruginosa in the state of Himachal Pradesh (India) - Naveen Minhas; Prakash Chand Sharma (Al Ameen Medical College, 2015)
Background: A prospective study was undertaken to detect metallo-β-lactamases (MBLs) and AmpC β-lactamases in Pseudomonas aeruginosa isolates recovered from patients at Indira Gandhi Medical College, Shimla (H.P). Objective: The study aimed at determining the prevalence of MBL and AmpC producing P. aeruginosa isolates. Material and Methods: A total of 180 isolates were preliminarily screened for their susceptibility to carbapenems (imipenem, meropenem, doripenem and ertapenem) and cefoxitin by in vitro antibiotic cultural sensitivity. The confirmation of MBL producing isolates was done by combined disc test and E test whereas AmpC production was confirmed by disc antagonism test and E test. Results and Conclusion: P. aeruginosa isolates (22.22%) were MBL producers on the basis of resistance to imipenem and meropenem while 60% were AmpC β-lactamase producers in preliminary screening test. Of the MBL producers, 50% isolates were confirmed by E test and 45% by combined disc test. However, only 13.33% were positive by both the confirmatory tests. By disc antagonism test, 46.33% isolates were detected as AmpC producers while 6.67% were positive by E test. It is interesting to note that of the 180 isolates examined, 14 (7.78%) were both MBL and AmpC producers. Both MBL and AmpC as mechanisms of resistance were thus, observed among the isolates of P. aeruginosa in the state of Himachal Pradesh. Emergence of such strains is of public health concern as such organisms pose therapeutic challenge.